International monetary reform: A critical appraisal of some proposals - Yung Chul Park; Charles Wyplosz (Asian Development Bank Institute (ADBI), 2012)
This paper reviews some of the current debates on the reform of the international monetary system. Despite its deficiencies, the United States (US) dollar will remain the dominant currency and Special Drawing Rights (SDR) cannot serve as either an international medium of exchange or a reserve currency. The International Monetary Fund (IMF) has changed its position to accept capital controls under certain circumstances. Refining control instruments better tuned to present day markets may bring about greater acceptance. The 2008-2009 global financial crisis has dimmed much of the earlier hope for the multilateralized Chiang Mai Initiative. The currency swap arrangements portend a new form of international cooperation. Finally, for the Group of Twenty (G20) to matter, the systemically important countries need to ensure the stability of their financial systems and economies.
Keywords: F32; F33; F42; 330; us dollars; special drawing rights; sdr; capital controls; currency swaps; g20; Internationales Währungssystem; Reservewährung; Kapitalverkehrskontrolle; Finanzkrise; Welt